Additive manufacturing of high-performance adsorbents for environmental use - Zheng, Alvin Lim Teik; Teo, Ellie Yi Lih; Marzuki, Omar Faruqi; Koo, Lee Feng; Wong, Tze Jin; Chung, Eric Lim Teik; Andou, Yoshito (Institute of Physics, 2025)
The emergence of 3D printing (additive manufacturing) has revolutionized the fabrication of advanced adsorbents. This review provides a comprehensive, analytical assessment of 3D-printed adsorbents, critically evaluating their materials, fabrication methodologies, and performance metrics. The materials discussed include polymers, metal-organic frameworks (MOFs), zeolites, biopolymers, carbon-based materials, and hybrid composites, all of which are evaluated in terms of their adsorption efficiency, selectivity, and functionalization strategies. This review also highlights future research directions, including computational modeling-driven design, multi-material printing strategies, and sustainable material innovations. As additive manufacturing technologies progress, their integration with adsorption science presents significant potential to transform environmental and industrial purification systems.